PENGARUH SUPERVISI KEPALA RUANG TERHADAP EFEKTIVITAS HANDOVER KEPERAWATAN DAN KESELAMATAN PASIEN : LITERAUR REVIEW - Azmi Sulintya Syahwa; Erna Aryanti; Ari Sunari; Lusi Herawati; Dini Hadianingsih (Jurnal Kesehatan, 2025)
Nursing handover is essential to ensure continuity of care and patient safety; however, it is often hindered by ineffective communication, low compliance, and lack of supervision. This review aims to examine the role of head nurse supervision and clinical supervision models in improving the quality of handovers based on SBAR/ISBAR. The methods applied include cross-sectional design, experimental pre–post test, literature review, as well as observation and interviews, with both quantitative statistical and qualitative thematic analyses. The findings show that supervision is significantly related to compliance and handover effectiveness, while the implementation of clinical supervision models enhances nurses’ self-efficacy, communication clarity, and handover skills. Monitoring and evaluation based on regulations and standard operating procedures (SOPs) also proved effective in improving service quality and reducing safety incidents. In conclusion, structured supervision plays a crucial role in optimizing nursing handover. Further research is recommended to explore the integration of digital technology into supervision and its impact on patient outcomes.